AI Implementation in Knowledge Management for Online News Media Case Study: GOnews.id - Mundzir, Ahmad; Purnama, Diki Gita; Mayasari, Iin (Brilliance: Research of Artificial Intelligence, 2024)
This study examines the role of artificial intelligence (AI) in enhancing knowledge management in the online news media industry, with a focus on GOnews.id as a case study. The industry faces unique challenges, including real-time information delivery and collaboration among dispersed teams. This research evaluates the impact of AI in addressing these challenges, improving operational efficiency, and enhancing content quality. Using qualitative methods, including in-depth interviews and document analysis, the study applied a thematic approach with NVivo 12 software. The findings reveal that AI facilitates faster information access, supports team collaboration, and maintains journalistic standards through automated editing tools. However, limitations such as high infrastructure costs, employee resistance, and AI's inability to fully grasp local contexts present challenges to its implementation. The study emphasizes the importance of using AI as a supportive tool rather than replacing human creativity and judgment. Key implications include AI's potential to enhance organizational competitiveness and responsiveness to audience trends. Recommendations include investing in robust infrastructure, providing employee training, and ensuring human oversight to balance technological efficiency with editorial nuance. By addressing these issues, the study provides valuable insights for media organizations seeking to optimize knowledge management strategies and offers a framework for leveraging AI to meet the demands of modern digital journalism.